Cricket : a viable industry - Adrien, Peter (2000)
Discusses the contribution of cricket to economic activities in the OECS countries. Analyses the impact of cricket on tourism and related activities. Focuses on the impact of cricket on the construction, telecommunications and transport sectors. Discusses some policies for planning, product development, infrastructural development and institutional strengthening.